Ultrasonic exfoliation of graphene in water: A key parameter study - Tyurnina, AV; Tzanakis, I; Morton, J; Mi, J; Porfyrakis, K; Maciejewska, BM; Grobert, N; Eskin, DG (Elsevier, 2020)
Liquid Phase Exfoliation (LPE) is an efficient method for graphene flake exfoliation and considered to be compatible with industrial production requirements. However, most of available LPE methods require the use of harmful and expensive solvents for chemical exfoliation prior to mechanical dispersion of the flakes, and therefore an additional step is needed to remove the contamination caused by the added chemicals, making the process complex, costly, unsafe and detrimental to the environment.